2011
DOI: 10.4276/030802211x12996065859409
|View full text |Cite
|
Sign up to set email alerts
|

Is it Time for a Mental Health Pathway in Undergraduate Programmes?

Abstract: The ten essential shared capabilities-a framework for the whole of the mental health workforce.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…These new and changing roles require graduating occupational therapists have knowledge and skills for generic mental health practice, along with a strong sense of what it is to be and practice as an occupational therapist to reduce the risk of graduates becoming overwhelmed or burnt out (Lloyd, King & Bassett, 2002;Scanlan, Still, Stewart & Croaker, 2010). This changing landscape of mental health service systems and practice prompted a call for the development of specific mental health occupational therapy educational streams in the United Kingdom (Bannigan et al, 2011). Although this proposal was controversial, it does highlight the importance of reviewing occupational therapy curricula to ensure that mental health educational needs are being adequately addressed.…”
Section: Introductionmentioning
confidence: 99%
“…These new and changing roles require graduating occupational therapists have knowledge and skills for generic mental health practice, along with a strong sense of what it is to be and practice as an occupational therapist to reduce the risk of graduates becoming overwhelmed or burnt out (Lloyd, King & Bassett, 2002;Scanlan, Still, Stewart & Croaker, 2010). This changing landscape of mental health service systems and practice prompted a call for the development of specific mental health occupational therapy educational streams in the United Kingdom (Bannigan et al, 2011). Although this proposal was controversial, it does highlight the importance of reviewing occupational therapy curricula to ensure that mental health educational needs are being adequately addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the introduction of a subspecialty of MH for OT students could be a way to expand OT students' knowledge about their role within MH. Similarly, Bannigan et al (2011) suggested separate education tracks for OT undergraduate students, one of which would be MH, and to allow for the foundation of OT skills and information, followed by one or two years devoted to the profession-specific skills and knowledge required in the chosen track.…”
Section: Discussionmentioning
confidence: 99%
“…No Reino Unido, Banningan et al 7 , debatendo sobre o currículo de TO, sugerem que a formação do terapeuta ocupacional inclua parte de formação base e parte de formação especialista, a fim de que o profissional esteja mais preparado para atender as exigências dos novos serviços de saúde mental, pois com as mudanças nas legislações, houve a inclusão de práticas que não tem sido contempladas na graduação como, por exemplo, a atenção junto à população com demência, serviços de crianças e adolescentes, atenção primária, doenças mentais leves, moderadas e severas, saúde mental da mulher. Gutman 8 considera que para contemplar as políticas públicas de saúde e as complexidades da pessoa com transtorno mental é necessário dar continuidade à revisão, exploração e investigação da prática da TO em saúde mental para torná-las, de fato, efetivas.…”
Section: U Ma Das Dimensões Presente Nas Diretrizesunclassified